Clinical and Genetic Findings of the First Report of PAPA Syndrome in Brazil - Sérgio Júlio Fernandes; Maria Isabel Valdomir Nadaf; Nauro Hudson Monteiro; Izabel Nazira Nadaf; Cleiton Ribeiro Lélis; Bianca Yumi Takano; Bárbarah Gabriella de Camargo Monteiro; Nyvea Gabriella de Camargo Monteiro; Olga Akiko Takano; Leonardo Oliveira Mendonça (Case Reports in Immunology)
Background. PAPA syndrome (MIM #604416) is a rare monogenic autoinflammatory disease genetically transmitted in an autosomal dominant trait that results from missense mutations in the proline-serine-threonine phosphatase-interactive protein 1 (PSTPIP1) gene located on chromosome 15 and is characterized by sterile pyogenic arthritis, pyoderma gangrenosum, and cystic acne. We describe the clinical and molecular findings of two related Brazilian patients with PAPA syndrome. Case Presentation. A 7-year-and-3-month-old boy with nonconsanguineous parents had had recurrent pyoarthritis since the age of 5 years and 8 months. During his last and long hospitalization, the lack of improvement with antibiotics, evidence of increased inflammatory activity, repeated arthrotomies, draining purulent fluid that had negative cultures, and the history of trauma, all on in a clinical background of pyoarthritis, led to the suspicion of an autoinflammatory syndrome. This was confirmed by the good clinical response to corticotherapy. Genetic sequencing confirmed the diagnosis of PAPA syndrome, with the pathogenic mutation c.688 G > A (p. Ala230Thr) in the PSTPIP1 gene present in the patient and in the mother. Conclusions. This case illustrates that in children with recurrent/recalcitrant sterile recurrent pyogenic arthritis/osteomyelitis, the possibility of an underlying immunological condition should be considered. In both, recurrent infections or recurrent inflammation, many genes involved in the inborn errors of immunity can be associated, and a correct and precocious diagnosis is necessary to avoid mobility and mortality. To the best of our knowledge, this is the first report of PAPA syndrome in Brazil.